The Implementation of Disability Rights Fulfillment in the General Election in Kuningan Regency Based on Law No. 7 of 2017 on General Elections - Erga Yuhandra; Iman Jalaludin Rifa'i; Suwari Akhmadhhian; Nabila Tri Nurcahyati; Nabila Tri Nurcahyati (UIN Siber Syekh Nurjati Cirebon, 2025)
This article examines the implementation of political rights for persons with disabilities during the General Election in Kuningan Regency, as outlined in Law Number 7 of 2017 on General Elections and Law Number 8 of 2016 on Persons with Disabilities. The research focuses on issues of accessibility and the effectiveness of electoral outreach. Using a normative legal method with a qualitative approach, this study examines legal frameworks, policy documents, and conducts interviews with relevant stakeholders. The findings reveal a significant gap between legal provisions and field implementation. Many polling stations remain physically inaccessible, and outreach programs often fail to consider the diversity of disability types. These barriers limit the participation of persons with disabilities in democratic processes. The study concludes that without accessible infrastructure and inclusive political communication, the right to vote and be elected cannot be fully realized for this marginalized group. It recommends stronger affirmative policies and collaboration between the General Election Commission, local authorities, and disability organizations topromote inclusive, non-discriminatory elections in line with human rights principles.